D and AD annual 2003. - Myerson, Jeremy, ....- (London : D and AD, 2003)
The D&AD annual is the showcase of all the best work from advertising and design in one year, the essential reference point for creative standards.
Keywords: Adverteren; Bedrijven; Creativiteit; Vormgeving